Design and Evaluation of a High Throughput Seismic Sensor Network - Tools for Planning, Deployment and Assessment - Manso, Marco (2017)
The rapid technological evolution in sensors, sensor platforms and networking is enabling the deployment of large sensor networks for "live" monitoring of seismic activity with high spatial resolution. In this regard, this paper describes our work in developing an online "High Throughput Seismic Sensor Network". We present the architecture and implementation comprising seismic sensors and servers (running data collection services) connected through internet-enabled technologies. We validate and assess the system, as well as identify bottlenecks, by means of experimentation. Based on the collected empirical data, we were able to identify methods and tools to support effective planning and implementation of sensor networks based on two main indicators: Sensor Network Transmission Rate (SNTR), which provides the overall network sensor data transmission throughput and thus an indication of the required network capacity; and CPU Sensor Network Performance Index (CSNPI), which provides an indication of a server capability to handle network sensor data. As we progress in our work to field deploy seismic sensor networks, we will continue to use these tools to plan and deploy future sensor networks, as well as assess improvements and modifications along the way.